2017
DOI: 10.1002/2017jc012793
|View full text |Cite
|
Sign up to set email alerts
|

Using remote sensing to detect the polarized sunglint reflected from oil slicks beyond the critical angle

Abstract: The critical angle at which the brightness of oil slicks and oil‐free seawater is reversed occurs under sunglint and is often shown as an area of uncertainty due to different roughness and surface Fresnel reflection parameters. Consequently, differentiating oil slicks from the seawater in these areas using optical sensors is a challenge. Polarized optical remote sensing techniques provide complementary information for intensity imagery with different physical properties and, thus, possess the ability to resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 65 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Remote sensing observations of sunglint can therefore provide information on aerosol properties (Kaufman et al, 2002;Ottaviani et al, 2008Ottaviani et al, , 2013 and on ocean surface slicks when polarimetric measurements are available (Ottaviani et al, 2012). Similar results for oil slick properties were subsequently obtained by Lu et al (2017) from spaceborne polarimetric observations by the POLDER (Polarization and Directionality of the Earth's Reflectances) instrument.…”
Section: Sunglint Heritage Studies: Remote Sensing and Ocean Surface mentioning
confidence: 52%
See 1 more Smart Citation
“…Remote sensing observations of sunglint can therefore provide information on aerosol properties (Kaufman et al, 2002;Ottaviani et al, 2008Ottaviani et al, , 2013 and on ocean surface slicks when polarimetric measurements are available (Ottaviani et al, 2012). Similar results for oil slick properties were subsequently obtained by Lu et al (2017) from spaceborne polarimetric observations by the POLDER (Polarization and Directionality of the Earth's Reflectances) instrument.…”
Section: Sunglint Heritage Studies: Remote Sensing and Ocean Surface mentioning
confidence: 52%
“…These reductions in measurement capabilities lead to a decrease in the retrieval accuracy of surface refractive indices from sunglint DoLP data, even in absence of aerosol scattering. Nevertheless, DoLP measurements of sunglint that were obtained by POLDER at a coarser accuracy (∼1%) in the NIR (870 nm) for ≤ 14 viewing angles have still proven useful in distinguishing between surface refractive indices retrieved for clean ocean waters and for oilslick covers (Lu et al, 2017). Hence, while PACE DoLP measurements of sunglint will not lead to the same retrieval accuracies for surface refractive index as RSP, they will likely contain information that can be used to not only detect and but also identify substances covering large sections of the ocean surface.…”
Section: Pace Updates (Inv Rt Studies): Polarimetric Remote Sensing Omentioning
confidence: 99%
“…In this case, this study provides complementary information to compensate or enhance normal non-polarized remote sensing on the earth surface. For example, remote monitoring and classification of crop structure parameters [7], sunglint detection on oceanic oil slicks [32] , and detection of land surface types with varying contamination [33] have been proven effective using DOLP.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of natural or anthropogenic surfactants in the microlayer therefore affects both the intensity and the polarisation state of the sun-glint signal. Recent studies showed that space-borne polarimetric measurements of sun glint can be used to estimate the presence of oil slicks from the change in refractive index between oiled and oil-free waters (Ottaviani et al, 2012;Lu et al, 2017). However, further studies are required to demonstrate whether this method could be applied to the detection of natural surfactants in order to provide estimations of the surfactant distributions and their impacts on the air-sea exchange processes at the global scale.…”
Section: Polarimetric and Multidirectional Sensorsmentioning
confidence: 99%